Analisis Mekanisme Pengendalian Internal Untuk Mewujudkan Akuntabilitas Dan Transparansi Pada Kantor Badan Kepegawaian Daerah Sumatera Utara - Thiffany Agun Salfiana; Sri Sudiarti; Kusmilawaty Kusmilawaty (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research is to find out the Analysis of Internal Control Mechanisms to Realize Accountability and Transparency at the North Sumatra Regional Civil Service Agency Office. The method used in this research is descriptive method with qualitative research. The data collection technique used in this study was through direct visits to the subjects who were the source of the data by conducting observations, interviews and documentation. The interviews conducted were direct interviews with the Head of the General Affairs and Personnel Subdivision, and the Head of the Apparatus Performance Assessment and Award Evaluation Division at the North Sumatra Regional Civil Service Agency. The results of this study indicate that the internal control system implemented at the Regional Civil Service Agency of North Sumatra is very good with a performance achievement of 90% -100%. The internal control mechanism at the North Sumatra Regional Personnel Agency can realize accountability and transparency, the availability of information that can be accessed easily is and the accountability written in the Government Agency Performance Report is proof of the realization of accountability and transparency.